The influence of grazing and indoor systems on goat milk, brined cheese and whey quality - Snežana Paskaš; Jelena Miočinović; Ivan Pihler; Ksenija Čobanović; Mila Savić; Zsolt Becskei (Mljekarstvo, 2023)
This study aimed to investigate whether diet and different goat production systems affect the quality of milk, white-brined cheese and whey. It also aimed to determine the suitability of goat's milk for the production of white-brined cheese. The physicochemical composition and hygienic quality of raw goat's milk were studied, as well as the fatty acid profile and nutritional indices of milk and white-brined cheese. Traditional white-brined cheeses were produced from bulk goat milk from two farms in three samples. The results confirmed that different husbandry systems and diets influence the physicochemical composition of goat milk and cheese and their fatty acid profile. Milk and cheese from grazing goats contained significantly more (p<0.05) fat, protein, total solids and a higher percentage of cheese yield. Nutritional indices were also more favourable, with a lower atherogenic (AI) and thrombogenic (TI) index and a higher health-promoting index (HHP) and hypocholesterolemic/hypercholesterolemic ratio (HH). Goat grazing contributed to a higher content of n-3 fatty acids in milk and cheese and thus to a lower n-6/n-3 ratio. Cheese-making efficiency and protein recovery in the curd (%REC) was better with pasture milk, whereas fat recovery was better with milk from housed goats. Consumers rated the unripened white cheeses from both production systems the highest. In addition, the production of white cheese with brine results in good quality whey with significant health benefits. Natural pasture provides significantly more benefits to goats than confinement, especially in the early stages of use. This contributes to the high nutritional value of goat's milk, cheese and whey.